Prevalence of inducible clindamycin resistance in erythromycin resistant clinical isolates of Staphylococcus aureus and CONS at tertiary care hospital - Thapa, Sangita; Sapkota, Lokendra Bahadur (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: The objective of this study was to isolate and identify Staphylococcus species from different samples clinical samples and to determine the current trend regarding the incidence and distribution of inducible clindamycin resistance in clinical isolates of Staphylococcus aureus and CONS. Materials & Methods: A total of 264 isolates of staphylococcus species were isolated from various clinical samples. Clinical samples were cultured and Staphylococcus species were identified using standard microbiological methods recommended by the American Society for Microbiology (ASM). Methicillin resistance was confirmed using cefoxitin and oxacillin disks. Inducible clindamycin resistance was identified using D-zone test. Results: Among 264 erythromycin resistant staphylococcus species, 213 (80.6%) were S. aureus and 51 (19.3%) were CONS. Out of 213 erythromycin resistant isolates of S. aureus, 140 (65.7%) were MRSA and 73 (34.2%) were MSSA whereas out of 51 erythromycin resistant isolates of CONS, 28 (54.9%) were MRCNS and 23 (45%) were MSCNS. Constitutive MLSB phenotype and Inducible MLSB phenotype was higher among both MRSA and MRCNS isolates. MS phenotype was more predominant among 11 (5.1%) MSSA and 5 (9.8%) MSCNS isolates compared to 9 (4.2%) in MRSA and 2 (3.9%) in MRCNS. Conclusion: The prevalence of constitutive & inducible clindamycin resistance in staphylococcus isolates was high among both MRSA and MRCNS. Hence the implementation of D-test routinely, will reveal the iMLSB & cMLSB phenotype & will guide the clinicians whether to use clindamycin in staphylococcal infections when erythromycin resistance is present.